Cloning and heterologous expression of subtilisin SAPN, a serine alkaline protease from Melghiribacillus thermohalophilus Nari2AT in Escherichia coli and Pichia pastoris. (June 2021) - Mechri, Sondes; Zaraî Jaouadi, Nadia; Bouacem, Khelifa; Allala, Fawzi; Bouraoui, Aicha; Ferard, Céline; Rekik, Hatem; Noiriel, Alexandre; Abousalham, Abdelkarim; Bouanane-Darenfed, Amel; Hacène, Hocine; Lederer, Florence; et al.
Graphical abstract: Highlights: Cloning sapN gene coding serine alkaline protease (SAPN) from Melghiribacillus genus. rSAPN was secreted by E. coli and more efficiently by Pichia pastoris. rSAPN enzymes produced by P. pastoris were more active than those produced by E. coli. rSAPN secreted by P. pastoris showed higher kcat / KM and DH than SAPN wild-type. This work has proven the potential industrial uses of rSAPN secreted by P. pastoris. Abstract: The sapN gene, encoding the extracellular subtilisin SAPN, a serine alkaline protease from Melghiribacillus thermohalophilus Nari2A T, was isolated, sequenced, and heterologously expressed in Escherichia coli BL21(DE3)pLysS using pUT57 and pTrc99A vectors and in E. coli BL21-AI™ using the Gateway™ pDEST™ 17 vector. Conversely, three cassettes encoding pre-pro-subtilisin (rSAPN/SP-Pro-M), pro-subtilisin (rSAPN/Pro-M), and the mature-subtilisin (rSAPN/M) were hyperexpressed in Pichia pastoris SMD1168 and X33 using the pPICZαC vector. rSAPNs were purified, characterized, and compared to wild-type SAPN. The deduced amino acid sequences exhibited high similarity with subtilisins from Bacillus strains. The highest sequence identity (96 %) was observed with the Bacillus licheniformis MP1 protease, with a 10-residue difference. Compared to SAPN and untagged rSAPNs, (His)6 -tagged enzymes showed the highest activity and stability at alkaline pH and high temperature, the highest hydrolysis degree on crab and shrimp by-products, and the best catalytic efficiency. It was found that His6 -rSAPN/SP-Pro-Ms expressed in P. pastoris strains was more active than those produced in E. coli . To initiate structure-function relationships, a 3D-model of the Pro-SAPN was built based on the available structures of common subtilisins. These data constitute a pivotal first step toward the creation of new efficient rSAPNs with enhanced catalytic properties and high potential for biotechnological and industrial uses.